Variability in egg size and population declines of Herring Gulls in relation to fisheries and climate conditions - Jessica L. Bennett; Ellen G. Jamieson; Robert A. Ronconi; Sarah N. P. Wong (Avian Conservation and Ecology, 2017)
Changes in clutch and egg size in many avian species have been linked to seasonal variation, female physiological state, and laying date during breeding season. These reproductive variables have also been linked to population status and habitat variables. Recent declines in Herring Gull (Larus argentatus) populations in the Atlantic region may be associated with environmental changes, fishery activities, or natural species interactions and fluctuations. We studied variability and trends in Herring Gull egg, clutch, and population size at a cluster of three islands of the Grand Manan Archipelago in the Bay of Fundy, Canada. A generalized linear model investigating variability in Herring Gull egg volume over a 28-year period (1988 to 2015) showed increasing egg volume since a low in 2000, significant positive correlations with regional fisheries landings, and weak interactions with sea surface temperature and the winter North Atlantic Oscillation (NAO) index. Herring Gull egg size decreased by 11.6% from 1988 to 2000, but both egg size and clutch size have increased significantly since 2001. A 2015/2016 population estimate of the three islands showed a 36% decline in Herring Gull numbers since 2001. Changes in annual and seasonal availability of various fishery related food sources, specifically decreasing Atlantic herring (Clupea harengus) and groundfish landings and increasing American lobster (Homarus americanus) landings, may be linked to these increases in reproductive variables. However, it appears that other factors may be influencing the declining gull population because despite increased availability of alternative food sources and increased clutch size and egg volume, there has been no documented increase in abundance. Interspecific interactions, anthropogenic activities, and climatic variability may also have a role in these population dynamics.